2016
DOI: 10.1016/j.ntt.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Early marijuana initiation: The link between prenatal marijuana exposure, early childhood behavior, and negative adult roles

Abstract: We investigated the associations among gestational factors including prenatal marijuana exposure (PME), child behavior at age 3, early age of onset of marijuana use (EAOM, < 15 years), and adult roles at 22 years. Participants were drawn from the Maternal Health Practices and Child Development (MHPCD) Project, a longitudinal study of prenatal substance exposure in offspring who have been studied for over 22 years since the prenatal phase. Data from the prenatal, birth, 3-, and 22-year phases (N=608) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
(52 reference statements)
0
17
0
1
Order By: Relevance
“…While there are some effects of prenatal marijuana exposure on neuropsychological functions in children, one has to exercise caution interpreting these effects. On one hand, though cognitive function effects due to prenatal marijuana exposure may be small in magnitude and often are not statistically significant, they may still have a significant impact on social outcomes for an individual in later life . Thus, it is important to fully understand the risks of exposure in the light of the changing culture and political climate surrounding marijuana.…”
Section: Commentmentioning
confidence: 99%
“…While there are some effects of prenatal marijuana exposure on neuropsychological functions in children, one has to exercise caution interpreting these effects. On one hand, though cognitive function effects due to prenatal marijuana exposure may be small in magnitude and often are not statistically significant, they may still have a significant impact on social outcomes for an individual in later life . Thus, it is important to fully understand the risks of exposure in the light of the changing culture and political climate surrounding marijuana.…”
Section: Commentmentioning
confidence: 99%
“…12 Maternal cannabis use has been associated with fetal growth reduction and decreased birth weight in newborns, 203 as well as with child development and behavior problems, poor school performance, and illicit drug use in children. [204][205][206][207] Case-control studies have found associations for different cancers among children when maternal cannabis use occurred during pregnancy, but provide weak evidence for causal associations. 137,[208][209][210]…”
Section: Special Risk Populationsmentioning
confidence: 99%
“…Marijuana use is associated with a number of adverse physical and behavioral health outcomes, including poorer performance on neurocognitive tests, lower educational attainment, and risk of marijuana use disorder (ie, abuse or dependence). [1][2][3][4][5] This is especially true for adolescent marijuana use initiates where the younger the age of first use, the more severe these outcomes tend to be. [1][2][3][4][5] Residential mobility and residential transience are recently identified potential risk markers for mental health and substance use disorders, including marijuana use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This is especially true for adolescent marijuana use initiates where the younger the age of first use, the more severe these outcomes tend to be. [1][2][3][4][5] Residential mobility and residential transience are recently identified potential risk markers for mental health and substance use disorders, including marijuana use disorder. [6][7][8] Residential mobility (ie, moving) has been shown to be a source of life stress and social disruption among adolescents that can interrupt friendship networks 9 and interfere with school attachment 10,11 and has been linked to poor mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%